Statistical optimization of xylanase production, using different agricultural wastes by Aspergillus oryzae MN894021, as a biological control of faba bean root diseases - Sherien M. M. Atalla (Egyptian Journal of Biological Pest Control, 2020)
Abstract Background Xylanase enzyme plays an important role in nature as being a part of protecting the environment from pollution. It has also various industrial applications. Main body of abstract Marine fungal isolate was recovered from red sea water at Sharm El-Sheikh province, Egypt, and tested for xylanase activity, using different agricultural wastes as a substrate. It was found that rice straw was the best substrate for xylanase production (0.37 U/ml). Thus, it was subjected for identification by 18S rDNA gene. The phylogenetic analysis results indicated that this fungal isolate belonging to Aspergillus species with a similarity of 99% and named as A. oryzae SS_RS-SH (MN894021). The regular two-level factorial design was used to optimize the important medium components, which significantly affected the xylanase production. The model in equation suggested optimal conditions of 2% of rice straw, 8 g/l of yeast extract, 4 g/l of (NH4)2SO4, 2 g/l K2HPO4, and 2.5 g/l MgSO4.7H2O for a maximum xylanase yield. The antifungal activity of crude xylanase on mycelial growth of some pathogenic fungi isolated from different hosts was investigated. The results showed that xylanase T1 had a potent antifungal activity than control. Greenhouse experiments indicated that all treatments with xylanase at different concentrations significantly decreased infection occurrence of beans, which have been effectively infected with root rot pathogens, compared to unprocessed control treatments. Short conclusion Xylanase yield increased 2.43-folds than initial screening. The xylanase had a potential antifungal activity both in vitro and under greenhouse conditions. The outcome of this study ensured that this fungal strain could be used as biological control for plant disease.